Odpowiedzi

Najlepsza Odpowiedź!
2010-03-27T22:13:43+01:00
2x+y=-3
4x+3y=-1

y = -2x-3
4x+3y=-1

4x+3(-2x-3)=-1
y = -2x-3

4x-6x-9 = -1 /+9
y = -2x-3

-2x = 10 /:(-2)
y = -2x-3

x = -5
y = -2x-3

y = -2*(-5)-3
x = -5

y = 7
x = -5

Proszę bardzo :)
1 5 1
2010-03-27T22:14:41+01:00
2x+y = -3
4x+3y = -1

y = -3-2x
4x+3(-3-2x) = -1

y = -3-2x
4x-9-6x = -1

y = -3-2x
-2x = -1+9

y = -3-2x
-2x = 8 |:(-2)

y = -3-2x
x = -4

y = -3-(2*-4) = -3+8 = 5
2010-03-27T22:17:40+01:00
{2x+y=-3}
4x+3y=-1

y= -3-2x
4x+3y=-1

y= -3-2x
4x +3 razy (-3-2x)=-1

y= -3-2x
4x - 9 -6x = -1

y= -3-2x
4x - 6x = -1 + 6x

y= -3-2x
-2x = 5 x |

i dalej nie wiem, sorry ;p
1 5 1